Effects of Arm Swing Exercise Program on HbA1C and Nutritional Status in Adults and Older Adults with Type 2 Diabetes: A Quasi-Experimental Study - Terathongkum S. (2023)
Regular physical activity is recommended for managing type-2 diabetes to achieve optimal glycemic control. Limited studies compared the effects of exercise between adults and older adults with type-2 diabetes. This quasi-experimental aim to investigate the effects of the Arm Swing Exercise Program on HbA1C and nutritional status among four groups of adults and older adults with type-2 diabetes. Eighty eligible participants were assigned to the experimental groups (20 adults and 21 older adults) receiving the 12week Arm Swing Exercise Program 30 minutes/day 5 day/week along with standard care, whereas the control groups (17 adults and 22 older adults) received standard care. Data were obtained, using the demographics questionnnaire, HbA1C, and nutritional status including waist circumference, body mass index, visceral fat, and skeletal muscle, before and after the Program. Paired t-tests, ANCOVA, and ANOVA were used for data analysis. The findings revealed no significant difference in HbA1C, waist circumference, body mass index, visceral fat, and skeletal muscle after receiving the Program between adults and older adults in the experimental groups. Older adults in the experimental group had significantly lower waist circumference than older adults in the control group, while adults in the experimental group had significantly lower waist circumference than adults and older adults in the control groups. This program was effective in only waist circumference reduction. Thus, nurses should encourage people with type-2 diabetes to continuously practice both the arm swing exercise and standard care to achieve glycemic control and better nutritional status. Further study should have more participants using randomized controlled trials and control other sensitive outcomes to the arm swing exercise.